Sistem Pendeteksi Debit Penampungan Air Berbasis IoT Menggunakan NodeMCU - Muhammad Habib; Supiyandi (Bulletin of Computer Science Research, 2023)
IoT-based reservoir water storage system using NodeMCU. This system can monitor and send information about water levels in real-time via the internet. The method used is to detect the water level in the reservoir using an ultrasonic sensor and control the water level using a relay. This system can help reduce economic losses caused by not being able to detect accurately by buoys which can cause an overflow of water in the reservoir. The method used in this research is the prototype method with stages of needs analysis, system design, implementation and evaluation. An IoT-based reservoir water storage system using NodeMCU ESP8266, relays, and ultrasonic sensors connected to the internet via Wi-Fi and controlled using the Blynk application on a smartphone. The aim of this research is that the system can provide notifications to users if the water level in the tank has reached certain limits, such as low, medium and full water conditions. As a result of this research, an IoT-based reservoir water storage system has been successfully developed using NodeMCU, relays, ultrasonic sensors, and the Blynk application which can monitor and send information about water levels in real-time via the internet.